4, 8-dicarboxyl-8, 9-iridoid-1-glycoside Promotes Neural Stem Cell Differentiation Through MeCP2. Issue 3 (3rd August 2022) - Wang, WeiBing; Liu, Zhen; Jing, BaoSheng; Mai, HaiMin; Jiao, Hong; Guan, Teng; Chen, DanGui; Kong, JiMing; Pan, Tao
Background: Borojó (Borojoa patinoi Cuatrec) fruit has recently been shown to have a variety of health benefit, but the mechanisms have been little studied. The aim of this study was to investigate the effect of 4, 8-dicarboxyl-8, 9-iridoid-1-glycoside (388) on proliferation and differentiation of embryonic neural stem cells (NSCs). Methods: NSCs were treated with 388 and stem cell differentiation was determined by western blotting and immunofluorescence staining. The role of MeCP2 in 388-mediated embryonic NSCs differentiation was examined. Results: The results showed that in the presence of mitogen when NSCs proliferated and maintained their multipotency, treatment with 388 did not affect the viability of NSCs. Following mitogen withdrawal to initiate NSC differentiation, treatment with 388 at the doses of 10 and 50 μg/mL significantly increased neural differentiation in both cortex and spinal cord-derived culture. 388 also significantly up-regulated MeCP2 expression. The expression of the neuronal and oligodendrocytic markers was enhanced after addition of 388 in the differentiation culture. However, knockdown of MeCP2 results in inhibition of NSC differentiation, and the pro-differentiation effect of 388 was mostly abolished. Conclusions: This study confirmed that 388 stimulates differentiation of NSCs and identifies its mechanism of action by upregulating MeCP2.